The failure of the antidepressant drug discovery process is systemic. (May 2013) - Hendrie, Colin; Pickles, Alasdair
Current antidepressants are crude compared with the ideal and patents on most have expired. There are therefore strong clinical and commercial pressures for new drugs to replace them. The prospects for this are, however, now markedly reduced as several major pharmaceutical companies have abandoned work in this area whilst many others have sharply decreased their research investment. These changes and the lack of progress over such a long period are indicative of a catastrophic systems failure which, it is argued, has been caused in large part by a logical flaw at the animal modelling stage. This tautology has served to lock the current antidepressant drug discovery process into an iterative loop capable only of producing further variations of that which has gone before. Drugs produced by this approach have proved to be only poorly effective in the context of the clinically depressed population as a whole. Hence, the inevitable failure of the current antidepressant drug discovery process has left little behind that can be salvaged. Therefore, it is suggested that this be urgently reformulated on more rational grounds using more appropriate species in new animal models based upon a thorough understanding of the behavioural expressions of depression in the clinic.